BERBAGAI SIKAP TERHADAP EKSISTENSI TUHAN PADA ERA INDUSTRI 4.0 - I Made Hartaka; Luh Putu Cita Ardiyani; Kadek Suciani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
In this era it is believed to be the era of industry 4.0 which brought many changes, especially in terms of technology. Humans are required to think critically to create innovations that can facilitate humans in their lives. Changes in the industrial era from 3.0 to 4.0 brought many new habits, mindsets and ways of life (impacted on changing habits, mindsets and new ways of life). This technological development has caused many changes in the mindset of people ranging from capitalism to materialism that tries to materialize God, this mindset makes a variety of perspectives about the existence of God, some believe in the existence of God, some do not believe in the existence of God and some are in between.